The interplay of Epigenetics, Gut Dysbiosis, Ama and Mandagni in Autoinflammatory pathogenesis of Ankylosing Spondylitis - a Scientific Review (AYUSHDHARA, 2025)
Ankylosing Spondylitis (AS) is a chronic autoimmune disorder primarily affecting the spine and sacroiliac joints, often leading to progressive stiffness, pain, and structural damage. Despite advances in conventional treatment, existing therapies remain largely palliative, with no definitive cure. This review explores the pathogenesis of AS through the interplay of epigenetics, gut dysbiosis, and metabolic dysfunction, emphasizing their correlation with Ayurvedic concepts such as Ama and Mandagni. Emerging evidence suggests that gut microbiome imbalances contribute significantly to chronic inflammation in AS, promoting immune dysregulation through antigenic mimicry and intestinal barrier dysfunction. Ayurveda describes a similar mechanism wherein improper digestion leads to Ama formation, which, under the influence of Mandagni, penetrates systemic circulation and triggers inflammatory cascades. The review integrates modern and Ayurvedic perspectives, proposing that Mandagni, or metabolic hypofunction, is the underlying factor connecting gut dysbiosis, chronic inflammation, and immune dysfunction. Furthermore, epigenetic modifications influenced by diet, lifestyle, and environmental factors act as triggers in genetically predisposed individuals, aligning with the Ayurvedic notion of Nidana (causative factors). A comparative analysis of modern and Ayurvedic treatment modalities highlights the potential role of Sopha and Vatavyadhi management in addressing the root causes of AS. Therapeutic interventions such as dietary modifications, gut microbiome restoration, detoxification (Shodhana), and Rasayana therapy may provide a holistic approach to disease prevention and management.